Head and neck cancer patients’ quality of life: A conceptual analysis - Mohamed Ludin, Salizar; Che Abdullah, Che Azunie (Nursing Programme School of Health Sciences Health Campus, Universiti Sains Malaysia, 2017)
Background of study: Treatment for head and neck cancer (HNC) may result in a variety of long-term consequences that might impair health-related quality of life (HRQOL). The aim of this study was to systematically review recent literatures on the quality of life HNC patients with a focus on physical and psychological issues and changes in the literature from the previous studies. Methods: A systematic literature search was completed in PubMed, Medline, Science Direct, CINAHL and Google Scholar by means of combined search terms ‘head and neck cancer’, ‘quality of life’, ‘health related quality of life’ and ‘association between quality of life and head and cancer’. The review was restricted to full articles published in English, bio-medical journals (2000 to 2016). Only studies analyzed QOL using questionnaires European Organization for Research and Treatment of Cancer (EORTC) QLQ C 30 and EORTC QLQ H and N 35 were included. Studies related to validation of the questionnaire and purely psychological studies were excluded. Results: The initial search yield 7050 original articles of which access to QOL of treatable HNC using EORTC questionnaire was 116. After considering the predetermined criteria, remaining 11 articles were included. These selected studies have revealed the enormous impact of HNC on survivors’ QOL. Although the global QOL of HNC cancer survivors recovered after treatment, problems with physical and psychological functioning may persist. Conclusion: A Further high-quality study was required to develop appropriate and effective interventions in this population and develop programs that are aimed at maximizing rehabilitation outcomes.